Worst case optimization for interfractional motion mitigation in carbon ion therapy of pancreatic cancer - Steitz, Julian; Naumann, Patrick; Häfner, Matthias; Sterzing, Florian (Radiation oncology, 2016)
The efficacy of radiation therapy treatments for pancreatic cancer is compromised by abdominal motion which limits the spatial accuracy for dose delivery - especially for particles. In this work we investigate the potential of worst case optimization for interfractional offline motion mitigation in carbon ion treatments of pancreatic cancer.
Gesehen am 07.11.2017